2022
DOI: 10.1371/journal.pone.0266001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of FIGO 2018 stage IB3/IIA2 cervical cancer treated by neoadjuvant chemotherapy followed by radical surgery due to lack of radiotherapy equipment: A retrospective comparison with concurrent chemoradiotherapy

Abstract: This study aimed to assess neoadjuvant chemotherapy’s clinical outcomes such as efficacy, toxicity, and survival outcomes followed by radical hysterectomy ((NACT-RS) among women with cervical cancer stage IB3 and IIA2, by comparing concurrent chemoradiotherapy (CCRT) and NACT-RS. The study retrospectively reviewed patients with (2018 FIGO) stage IB3 and IIA2 cervical cancer who received preoperative neoadjuvant chemotherapy followed by NACT-RS or concurrent chemoradiotherapy (CCRT). The outcome measures were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In LACC, cisplatin-based concurrent radiation has a better the disease-free survival (DFS) rate than NACT followed by radical surgery; however, no statistically signi cant differences are observed in the overall survival (OS) rates 8 . NACT followed by radical surgery has demonstrated an OS rate similar to that observed with concurrent radiation in patients with stage IB3 and IIA2 cervical cancer, with no increase in side effects 9 . In patients with comparable survival, approximately 25-30% of patients who undergo surgery after NACT still require adjuvant radiotherapy or chemoradiotherapy.…”
Section: Introductionmentioning
confidence: 56%
“…In LACC, cisplatin-based concurrent radiation has a better the disease-free survival (DFS) rate than NACT followed by radical surgery; however, no statistically signi cant differences are observed in the overall survival (OS) rates 8 . NACT followed by radical surgery has demonstrated an OS rate similar to that observed with concurrent radiation in patients with stage IB3 and IIA2 cervical cancer, with no increase in side effects 9 . In patients with comparable survival, approximately 25-30% of patients who undergo surgery after NACT still require adjuvant radiotherapy or chemoradiotherapy.…”
Section: Introductionmentioning
confidence: 56%
“…Studies have shown that tumor diameter is associated with prognosis. For locally advanced cervical cancer with CCRT, large tumor diameter and non-HPV16/18 genotypes are independently associated with poor PFS [5,11,12], also there is a study suggest that HR-HPV infection was not a prognosticator of 5-year OS [13]. In this study, large tumor diameter and HPV infection were not found to be independent risk factors affecting PFS, which may be because the included patients in this study were cervical cancer patients receiving NACT, and tumor diameter was large, so the difference of tumor diameter and HPV infection had no significant effect on prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have concluded whether NACT improves the prognosis of patients. Zeng [5] evaluated the efficacy of NACT on patients with stage IB3 and stage IIA2 cervical cancer by comparing the two treatment methods of CCRT and Next-RS, and observed the 5-year survival rate and complication rate of patients in the two groups. The results showed that the survival period of patients treated with Next-RS was similar to that of patients receiving CCRT.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Radiotherapy and chemotherapy have gained clinical recognition as fundamental treatment methods, often administered in tandem. [5] Despite their relatively significant clinical effects, accumulating research suggests that these therapies are associated with numerous complications, toxicities, and side effects, [6] including myelosuppression, [7][8][9] gastrointestinal reactions, [10] radiation proctitis, and radiation cystitis. [11] However, over time, cervical neoplasms may develop resistance to traditional treatments and certain individuals may prove unresponsive to chemotherapy or radiotherapy.…”
Section: Introductionmentioning
confidence: 99%